Type of occurrence classification system - Australia. National Occupational Health and Safety Commission (Canberra : The Commission, 2004)
"The Type of Occurrence Classification System (TOOCS1.0) was developed for use in coding details of workers' compensation cases reported to workers' compensation agencies. The third edition of TOOCS (TOOCS3.0) has been revised and updated taking into account feedback received from users"--p. 1.
Coding guidelines -- Selected examples of injury and disease occurrences -- Nature of injury/disease classification -- Bodily location of injury/disease classification -- Mechanism of incident classification -- Agency of injury/disease classification.
"March 2004".
"First edition 1990, Second ed. 1999, Rev. 2002"--T.p. verso.
Includes index.
Also available in an electronic version on the Internet. Address as of 09/11/03: http://www.nohsc.gov.au/PDF/Statistics/toocs3.pdf
System requirements: Adobe Acrobat Reader required to view/print PDF files.
Keywords: Occupational diseases -- Australia -- Classification -- Handbooks, manuals, etc; Occupational diseases -- Reporting -- Australia -- Handbooks, manuals, etc; Industrial accidents -- Reporting -- Australia -- Handbooks, manuals, etc; Industrial accidents -- Australia -- Classification -- Handbooks, manuals, etc